Insulin growth factor 1 like receptor (IGF-1R). Issue 1 (December 2016) - Iyer, Gopal; Price, James; Bourgeois, Shay; Armstrong, Eric; Huang, Shyhmin; Harari, Paul
Abstract Background The epidermal growth factor receptor (EGFR) is frequently overexpressed in head and neck squamous cell carcinoma (HNSCC) and several other human cancers. Monoclonal antibodies, such as cetuximab that block EGFR signaling, have emerged as valuable molecular targeting agents in clinical cancer therapy. Prolonged exposure to cetuximab can result in cells acquiring resistance by a process that remains incompletely understood. Methods In this study, we analyzed the immediate early molecular response of cetuximab on physical interactions between EGFR and Insulin growth factor 1 like receptor (IGF-1R) in head and neck cancer cells that are resistant to cetuximab. Co-immunoprecipitation, small molecule inhibitors against phospho-Src and IGF-1R, quantitative western blot of EGFR and Src phosphorylation, cell proliferation assays were used to suggest the role of IGF-1R mediated phosphorylation of specific tyrosine Y845 on EGFR via increased heterodimerization of EGFR and IGF-1R in cetuximab resistant cells. Results Heterodimerization of EGFR with IGF-1R was increased in cetuximab resistant HNSCC cell line UMSCC6. Basal levels of phosphorylated EGFR Y845 showed significant increase in the presence of cetuximab. Surprisingly, this activated Y845 level was not inhibited in the presence of Src inhibitor PP1. Instead, inhibition of IGF-1R by picropodophyllin (PPP) reduced the EGFR Y845 levels. Taken together, these results suggest that heterodimerization of EGFR with IGF-1R can lead to increased activity of EGFR and may be an important platform for cetuximab mediated signaling in head and neck tumors that have become resistant to anti-EGFR therapy. Conclusions EGFR-IGF-1R interaction has a functional consequence of phosphorylation of EGFR Y845 in cetuximab resistant HNSCC cells and dual targeting of EGFR and IGF-1R is a promising therapeutic strategy.